Modern models of state regulation of tourism activities: the international practice - Гостюк, Василь Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the scientific article the current model of state regulation of tourist activities is considered. Methodological recommendations for improvement of the model of regulation of tourism activities in Ukraine are formed. Attention is paid to the tourist product’s quality providing. International practice shows that the efficiency of state management of tourism largely depends on the model of state participation in the regulation of this important component of the national economy. It’s mentioned in the article that there are a number of problems in Ukraine that do not contribute to the development of the tourism industry and require the development of new approaches to the formation of an effective regulatory mechanisms, particularly in the area of domestic tourism. The author emphasizes that although the necessity of state control in the sphere of tourism, its implementation requires a special approach. One the one hand, the tourism sector as a diversified industrial complex needs to coordinate its economic activity; on the other hand, excessive state presence and regulation inhibits the manifestation of entrepreneurial initiative, which underlies the formation and development of market relations. In addition, the tourism sector is of great economic, political and socio-cultural importance for each country, resulting in the formation of state governments quite complex process. International tourism law has a great impact on the development of tourism, the emergence of new areas of the tourism activity. Simultaneously with the development of the market of tourist services in recent years the activities associated with the provision of consumer rights to use immovable property located at various resorts in the world, the so-called vacation club, have spread. This type of service is known as «timesharing» and «vacation club». International experience of state regulation of tourism development suggests that some elements of state regulatory mechanisms should be used in the development of tourist industry of Ukraine, taking into account its historical, cultural and natural potentials. Analysis of the role of the state in the organization and development of tourism activities in different countries of the world allows to select the types of models of public participation in the regulation of tourism as a component of the local economies.